Helicobacter pylori‐associated peptic ulcer disease: A retrospective analysis of post‐treatment testing practices. Issue 6 (23rd September 2018) - Feder, Rachel; Posner, Shai; Qin, Yi; Zheng, Jiayin; Chow, Shein‐Chung; Garman, Katherine S.
Abstract: Background & Aims: Guidelines recommend that patients with Helicobacter pylori ( H. pylori )‐associated peptic ulcer disease (PUD) receive H. pylori eradication therapy followed by post‐treatment testing to prove eradication; however, post‐treatment testing rates are suboptimal and barriers to testing are poorly understood. Our aim was to identify factors that predicted receipt of post‐treatment testing. Methods: We performed a retrospective cohort study of 152 patients with H. pylori ‐associated PUD diagnosed between 2007 and 2015 at a large tertiary medical center in the United States, who received standard eradication therapy and ambulatory follow‐up within one year. The primary outcome of interest was receipt of post‐treatment testing. Logistic regression models compared post‐treatment testing rates in those diagnosed while outpatient vs inpatient, patients with vs without repeat endoscopy, and patients with vs without gastroenterology (GI) clinic follow‐up. Propensity scores controlled for age, sex, race, ulcer location, and symptom persistence. Results: Among 152 patients, 67 (44%) patients received post‐treatment testing. There were significant differences in post‐treatment testing rates in those diagnosed as outpatients vs inpatients (57% vs 33%; OR 3.87, P  = 0.001) and in patients with vs without GI follow‐up (62% vs 11%; OR 9.85, P  < 0.0001). Conclusions: The rate of testing for eradication after treatment in patients with H. pylori ‐ associated PUD was low. However, this was significantly improved in patients who have GI follow‐up and whose diagnosis was made in the outpatient setting. Our study demonstrates a clear opportunity for quality improvement initiatives.